2019
DOI: 10.22605/rrh4200
|View full text |Cite
|
Sign up to set email alerts
|

Continued development of the Rural Active Living Perceived Environmental Support Scale (RALPESS): preliminary evidence for validity among American Indians

Abstract: Introduction: The prevalence of childhood cardiovascular disease (CVD) risk factors often increases in more rural geographic regions in the USA. However, research on the topic often has conflicting results. Researchers note differences in definitions of rurality and other factors that would lead to differences in inference, including appropriate use of statistical clustering analysis, representative data, and inclusion of individual-level covariates. The present study's objective was to examine CVD risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This finding may have resulted partly from a measurement issue for the home/neighborhood domain. Previous qualitative research in the same region found that much PA around the home occurred through yard work, which would not have been captured in the home/neighborhood measure because of its focus on walkability (25). Notably, perceptions of the various domains were mainly neutral to negative across the board.…”
Section: Discussionmentioning
confidence: 94%
“…This finding may have resulted partly from a measurement issue for the home/neighborhood domain. Previous qualitative research in the same region found that much PA around the home occurred through yard work, which would not have been captured in the home/neighborhood measure because of its focus on walkability (25). Notably, perceptions of the various domains were mainly neutral to negative across the board.…”
Section: Discussionmentioning
confidence: 94%
“…According to a WHO 2016 report, the prevalence of obesity has increased by nearly 50% in Africa since 2000 [34]. Reducing the risk and the frequency of excess weight must be one of the targets in hypertension prevention and control in children and adolescents [35].…”
Section: Discussionmentioning
confidence: 99%
“…This association is well known and seems more important in female adolescents and young ladies [10, 18-19, 31, 32, 45] . Waist size, which was not assessed, is also linked to the prehypertension risk, even in the absence of excess weight [31][32][33][34][35][36][37][38][39][40][41][42]. Weight loss is recommended by the NHBP to reduce the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to a WHO 2016 report, the prevalence of obesity has increased by nearly 50% in Africa since 2000 [33]. Reducing the risk and the frequency of excess weight must be one of the targets in hypertension prevention and control in children and adolescents [34].…”
Section: Hypertensionmentioning
confidence: 99%
“…This association is well known and seems more important in the girls a,d young women [10, 17-18, 30, 31, 44] . Waist size, which could not be studied in this work, is also linked to the prehypertension risk, even in the absence of excess weight [30][31][32][33][34][35][36][37][38][39][40][41]. Weight loss is recommended by the NHBP to reduce the risk of hypertension.…”
Section: Prehypertensionmentioning
confidence: 99%